Pengaruh Bermain Puzzle dan Dukungan Sosial Guru Terhadap Resiliensi Anak Usia 5-6 Tahun di Pendidikan Anak Usia Dini Kenanga Raya Medan - Tetti Dorlima Tiodora Nainggolan; Asih Menanti; Amanah Surbakti (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine: To determine the effect of playing puzzles and PAUD teacher social support on the resilience of children aged 5-6 years at PAUD Kenanga Raya Medan for the 2020/2021 academic year. This research method is a quantitative descriptive correlational type by placing the research variables in two groups, namely the independent variable and the dependent variable. The population of this research is PAUD Kenanga Raya Medan children. The sampling technique used was the purposive sampling technique with the selected sample size of 30 children, the data collection method used the puzzle playing observation sheet and the parental social support observation sheet, and the child resilience observation sheet. Analysis of research data shows that (1) there is a significant effect between playing puzzles on the resilience of children aged 5-6 years at PAUD Kenanga Raya Medan as indicated by a significance value of 0.047<0.05; (2) there is a significant effect between teacher social support on the resilience of children aged 5-6 years in PAUD Kenanga Raya, which is indicated by a value of 0.034 <0.05; (3) there is an effect of playing puzzles and teacher's social support on the resilience of children aged 5-6 years at PAUD Kenanga Raya.